Estrutura de metacomunidades de peixes em uma microbacia da Mata Atlântica - Almeida, Rodrigo da Silva (Universidade Federal de São Carlos, 2013)
The concept of metacommunities incorporates the influence of local and regional factors in structuring communities and has supported recent approaches related to patterns of distribution, abundance and species interactions. Within this concept, the species sorting model that assumes that a community is governed only by local factors, while the mass effect model assumes that a community is governed by local and regional effects. A stream system has a hierarchical dendritic network, in which the upstream water bodies are smaller and tend to increase in the downstream direction due to the connection with other streams. To stream fish, the dispersion process by the channel reveals the importance of regional factors on the structure of metacommunities, while habitat heterogeneity acts locally, and may reveal boundaries between metacommunities. This study aims to determine whether there is the formation of metacommunities along the longitudinal gradient and models which explain this structure. We captured fish populations and raise environmental information in three streams (15 reaches of 70 m) of a small watershed of the Atlantic. A principal component analysis (PCA) was applied to describe the environmental gradient and to verify the occurrence of this metacommunities apply a gradient elements of metacommunities analysis (EMS). The pattern of distance decay relationships (DDR) was used to verify whether metacommunities are influenced by the effects of local and / or regional and so seek explanations for the pattern found. We can say that there are two distinct communities (clementsian pattern of metacommunities), one nearest the mouth with no defined pattern caused by a process mass effect and a more flush with standard board from a species sorting process. Distinguish these communities is of great interest to conservation purposes and the development of strategies for biomonitoring. For example, for communities downstream, where the environmental changes caused by urbanization are more prevalent and there is the possibility of removing this source of environmental impact, ensure connectivity of streams is a good strategy since the species moving more intensely and are very dependent on the source of colonization. On the other hand, communities further upstream, even if there is a disconnect with the region downstream promoted by the damming of streams for water harvesting, these communities will remain theoretically provided that local conditions are guaranteed, ie, there is a pressing conservation environmental integrity of these excerpts.
Metacommunities structures of fish in a watershed in the Atlantic Forest
Keywords: Ictiologia; Peixes de água doce - Mata Atlântica; Bacia hidrográfica; Hotspot; Processos de dispersão; Riachos; Dispersal processes; Fishes; Hotspot; Rain Forest; Streams; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA TEORICA